2004
DOI: 10.1007/s10592-004-1860-2
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic consequences of a recent bottleneck in the Amur tiger of

Abstract: The Amur tiger, Panthera tigris altaica, is a highly endangered felid whose range and population size has been severely reduced in recent times. At present, the wild population is estimated at 490 individuals, having rebounded from the 20-30 tigers remaining following a severe bottleneck in the 1940's. The current study presents preliminary data on the patterns and levels of genetic variation in the mitochondrial DNA control region using DNA extracted from non-invasively sampled faecal material, collected thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 27 publications
(26 reference statements)
5
41
1
Order By: Relevance
“…However, such ancient events might be substantially overarched by the much more recent population decline, leading to a loss of genetic diversity. Such a loss was previously reported in wild Amur tiger (P. tigris altaica) populations, where mtDNA variation was only found in captive specimens, but not in the wild (Russelo et al 2004). In our study, haplotype TIG* 9 was only found in white tiger specimens from Zoo Delhi representing the extinct population from Rewa (Central India).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…However, such ancient events might be substantially overarched by the much more recent population decline, leading to a loss of genetic diversity. Such a loss was previously reported in wild Amur tiger (P. tigris altaica) populations, where mtDNA variation was only found in captive specimens, but not in the wild (Russelo et al 2004). In our study, haplotype TIG* 9 was only found in white tiger specimens from Zoo Delhi representing the extinct population from Rewa (Central India).…”
Section: Discussionsupporting
confidence: 69%
“…This is lower than in a comparable study in more temperate regions (Russelo et al 2004;86.3%), possibly due to different climatic conditions which can influence DNA quality in scat samples (Nsubuga et al 2004).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…In it, sequences were divided into two clades. Pati-DRB*1, Papa-DRB*1, Papa-DRB*2 and Papa-DRB*3 (Russello et al, 2004). In addition, researchers also found similar results in Cheetah and lion (Panthera leo) population (O'Brien et al, 1983;Packer et al, 1991).The varied levels of MHC genes on population were regard as the important factors of immune response to various pathogens and disease.…”
Section: Phylogenetic Analysismentioning
confidence: 67%
“…Therefore, its low dispersal ability (Ureña-Aranda et al 2015), low genetic variability (Ureña-Aranda and Espinosa de los Monteros 2012), and fragmentation and loss of grassland H. mutica are the main threats for the Bolson tortoise, because these factors favor isolation of the populations of this tortoise by intensifying the low genetic variability of the species. These conditions promote less resistance to extreme temperatures, drought events, change in food availability, emerging diseases, among other features, thus causing population extinction (Hoelzel et al 2002;Russello et al 2004;Zhang et al 2004).…”
Section: Discussionmentioning
confidence: 99%